Government communication pieces on HIV pre-exposure (PrEP) and post-exposure (PEP) prophylaxis (2016-2019): analysis of their content and circulation among gay men, trans women/travestis, and sex workers - Mora, Claudia; Nelvo, Romário; Monteiro, Simone (Saúde e Sociedade, 2023)
This article analyzes the advertisement of pre-exposure (PrEP) and post-exposure (PEP) prophylaxis treatment for HIV considering the historical role of AIDS prevention campaigns in Brazil. A total of 24 pieces of communication on PrEP, PEP, and Combined Prevention, produced from 2016 to 2019 and published on the website and social media of the Brazilian Ministry of Health were analyzed in addition to the testimony of 30 users of prophylaxis – including gays, trans women/travestis, and sex workers – in the metropolitan region of Rio de Janeiro. The materials were classified according to type, year, audience, and access information, and the results were interpreted from four axes: contextualization of the communication pieces and the experience of the interlocutors with the information; sexuality and risk; gender, emotions, and moralities; and condom displacements. The analysis indicated the erasure of expressions of sexuality and the predominance of an abstract and structured language, presupposing a rational and individualistic public, with condoms associated with “sexual risk.” Users’ reports regarding the advertisement of information on these prophylaxis reveals its insufficiency. We conclude that the potential of information and communication campaigns, guided by the sociocultural reality of social segments, has been little explored, compromising access to prophylaxis. Thus, the biomedicalization of prevention and the advance of conservatism in Brazil hinder the Brazilian response to AIDS.